1989
DOI: 10.1016/0014-5793(89)80289-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence‐specific adducts of adriamycin and mitomycin C

Abstract: Adriamycin and mitomycin C were reduced by xanthine oxidase/NADH in the presence of a DNA template comprising a stable initiated ternary transcription complex derived from the lac UV5 promoter. Subsequent elongation of the transcription complex treated with mitomycin C revealed high levels of terminated transcripts one nucleotide prior to G residues on the coding strand (i.e. at X of XpC sequences of the non-coding strand). Lower levels of termination occurred with adriamycin, and these were also one nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Our ability to produce and purify large amounts of stable covalent Adriamycin-DNA adduct in solution has allowed a more direct structural comparison of these adducts than previously possible by MS. CH 2 O-and Tris͞Fe(III)͞DTT-mediated Adriamycin-DNA adducts were formed on the selfcomplementary hexanucleotide d(ATGCAT) 2 , containing only a single potential site for adduct formation. Isolation and purification of the respective adduct and analysis by high-field 1 H NMR indicated that the CH 2 O-and Tris͞Fe(III)͞DTT-mediated Adriamycin-DNA adducts are structurally identical (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our ability to produce and purify large amounts of stable covalent Adriamycin-DNA adduct in solution has allowed a more direct structural comparison of these adducts than previously possible by MS. CH 2 O-and Tris͞Fe(III)͞DTT-mediated Adriamycin-DNA adducts were formed on the selfcomplementary hexanucleotide d(ATGCAT) 2 , containing only a single potential site for adduct formation. Isolation and purification of the respective adduct and analysis by high-field 1 H NMR indicated that the CH 2 O-and Tris͞Fe(III)͞DTT-mediated Adriamycin-DNA adducts are structurally identical (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 3 shows the anomeric-aromatic portion of the two-dimensional 1 H NOESY spectrum of the Adriamycin-DNA adduct formed on d(ATGCAT) 2 . From the connectivity pattern in this region, it is clear that only one reaction product is present, in which a single Adriamycin molecule is covalently bound per DNA duplex.…”
Section: Incorporation Of 13 C -Labeled Ch 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…[100] Phillips, White, and Cullinane implemented an in vitro transcription assay exhibiting blockage of transcription by E. coli RNA polymerase at specific DNA sites when mitomycin C was reduced by xanthine oxidase/NADH, that showed selectivity for XpC sequences of the non-coding strand, corresponding to G selectivity of the coding strand. [101] Through experiments in the Hopkins lab involving sequence-random cleavage of MMC cross-linked DNA, the sequence specificity of the cross links was determined at single nucleotide resolution to be at the G of 5′- d(CG) in strong preference to 5′-d(GC). [102] Crothers simultaneously utilized a gel electrophoresis assay yielding identical results.…”
Section: Biochemistrymentioning
confidence: 99%
“…1) that lies in the minor groove without forming any bonds to DNA (4), although eventually it may also form covalent adducts with DNA (36,37).…”
Section: Discussionmentioning
confidence: 99%